2020
DOI: 10.2174/1389200221666200120121919
|View full text |Cite
|
Sign up to set email alerts
|

Genistein: Its Role in Breast Cancer Growth and Metastasis

Abstract: Background: Genistein being a phytoestrogen imitates the characteristics of estrogen, which can be useful to treat conditions by reducing the estrogen levels at the time of menopause, osteoporosis and high risk for breast cancer. Objective: The superior binding of genistein to ERβ might help in reducing breast malignancy risk. Conclusion: Genistein induces cell cycle arrest, anti-metastatic properties and ultimately affects the breast cancer cell growth by multiple mechanisms. Genistein-mediated anti-prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The EGFR/Akt/NFκB pathway modulation play a role in cell differentiation [58], which leads to cancer cell death. With genistein, the activity of Akt is suppressed, promoting the deactivation of downstream signaling pathways, including NF-κB [2,59]. This was demonstrated by the electrophoretic mobility shift assay in MDA-MB-231 cells, along with inhibition in the activation of Akt by preventing EGF signal triggering [59].…”
Section: Cell Cycle Arrest and Anti-proliferative Mechanismmentioning
confidence: 97%
See 1 more Smart Citation
“…The EGFR/Akt/NFκB pathway modulation play a role in cell differentiation [58], which leads to cancer cell death. With genistein, the activity of Akt is suppressed, promoting the deactivation of downstream signaling pathways, including NF-κB [2,59]. This was demonstrated by the electrophoretic mobility shift assay in MDA-MB-231 cells, along with inhibition in the activation of Akt by preventing EGF signal triggering [59].…”
Section: Cell Cycle Arrest and Anti-proliferative Mechanismmentioning
confidence: 97%
“…Several in vitro and in vivo studies have attempted to understand and gain a better insight into the mechanisms underlying the biomedical properties of genistein [2][3][4]. The isoflavonoid has been analyzed and previously reviewed for its neoplastic potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to better understand the mechanisms of its beneficial effects in different diseases. In vivo and in vitro analyses indicated that genistein can modulate numerous signaling cascades in several types of cancer cells, that results in decreased cell viability, and promotion of cell death [ 5 ]. Figure 1 illustrates the molecular interactions of genistein in different cellular pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Genistein directly suppresses the activity of Akt and therefore this substance promotes the inactivation of its downstream signaling pathways, including nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [ 5 – 7 ]. The electrophoretic mobility shift assay further demonstrated that treatment with genistein directly inactivates NF-κB in MDA-MB-231 cells [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…GE acts as a potent chemopreventive and therapeutic agent against various types of cancers including breast, prostate, and lung cancer [9,10]. The mechanisms by which GE elicits its anti-carcinogenic properties involve inhibition of cellular proliferation, angiogenesis, and metastasis as well as induction of apoptosis, differentiation, and cell cycle arrest at the G2-M phase [11][12][13]. Specifically, it is known to inhibit breast carcinogenesis by regulation of several signaling pathways such as downregulation of VEGF, HIF-1α, MMPs, fibronectin, JNK, ERK/PI3K/AKT axis and upregulation of p21 [11,13].…”
Section: Introductionmentioning
confidence: 99%